Daratumumab, cyclophosphamide, bortezomib and dexamethasone for non-transplant eligible myeloma (AMaRC 03-16) - Peter Mollee; John Reynolds; Wojt Janowski; Hang Quach; Philip Campbell; Simon Gibbs; Sophie Lee; Edwin Lee; Kerry Taylor; Tara Cochrane; Craig T. Wallington‐Beddoe; Fiona Kwok; et al. (2024)
In newly diagnosed transplant-ineligible patients with myeloma, daratumumab has improved outcomes when added to the standard-of-care regimens. In a randomized trial, we tested whether similar improvements would be observed when daratumumab was added to the bortezomib, cyclophosphamide, and dexamethasone (VCD) regimen. Transplant-ineligible patients with untreated myeloma were randomized to receive VCD or VCD plus daratumumab (VCDD). A total of 121 patients were randomized: 57 in the VCD arm and 64 in the VCDD arm. Baseline characteristics were balanced between the 2 arms. The median progression-free survival (PFS) was 16.8 months (95% confidence interval [CI], 15.3-21.7) and 25.8 months (95% CI, 19.9-33.5) in the VCD and VCDD arms, respectively (hazard ratio, 0.67; log-rank test P = .066). In a preplanned analysis, it was demonstrated that the daratumumab-containing arm showed a significant improvement in PFS from 18 months onward, based on estimates at fixed time points after randomization. The proportions of patients who were progression-free at the following time points were: 18 months, 48% vs 68% (P = .0002); 24 months, 36% vs 52% (P = .0001); and 30 months, 27% vs 41% (P < .0001) in the VCD and VCDD arms, respectively. The best overall response and very good partial response rate were significantly higher in the daratumumab arm compared with the VCD and VCDD arms, respectively (65% vs 86%, P = .007; and 28% vs 52%, P = .009). Seventy-two percent of the VCDD patients completed the 9 cycles of induction therapy with no grade 3 or 4 peripheral neuropathy adverse events. This study supports VCDD as an option for the initial treatment of transplant-ineligible patients with myeloma. This trial was registered at the Australian New Zealand Clinical Trials Registry (ACTRN12617000202369).